Saxon England According to the Saxon Chronicle - Camden, William (Britannia: or, a Chorographical Description of the Flourishing Kingdoms of England, Scotland, and Ireland, and the Islands Adjacent, Vol. 1, 1806)
Map of Saxon England based upon descriptions in the Anglo-Saxon Chronicle, a collection of annals in Old English chronicling the history of the Anglo-Saxons.
Keywords: Great Britain; Maps; Britannia (Camden, William); England; Islands; Anglo-Saxon chronicle